PENGARUH PERPUTARAN MODAL KERJA TERHADAP RETURN ON EQUITY (ROE) DI PT. UNILEVER TBK, JAKARTA - Djoko Maryanto; Iqbal Rafif (JURNAL LENTERA AKUNTANSI, 2021)
This study aims to produce information in the form of a more in-depth explanation of the influence of working capital turnover on return on equity. And get the results from the processed data about how much influence the working capital turnover have on return on equity. The research method used in this study, the data obtained both quantitative and qualitative in nature were examined using a descriptive method, namely with a quantitative approach to the form of financial reports for working capital turnover quarters of 2011-2019.Based on calculations with a simple linear regression equation Y = 0.058 + 0,182X means that if the value of  working capital turnover is 0, the value of return on equity is 0.058%  and if the working capital are Rp. 1, - the return on equity will increase by 0,182%. R value = 0.730  means that the relationship between working capital turnover and return on equityt is high. While the value of R2 = 0.533 or 53.3% means that the return on equity is influenced by working capital turnover by the remaining 53.3% by 46.7% influenced by other variables not examined. While the T test results obtained sig 0.003> 0.05 then H0 is accepted, and based on the T test t(6.230) which means that the variable t value is higher than t table that is( 2.03224) proving that the working capital turnover have relationship on the return on equity. Keywords: Working Capital Turnover, Return On Equity (ROE)